Hard alloy material containing graphene oxide and preparation method thereof
GO/Co composite powder was prepared through hydrothermal reaction and high-thermal reduction calcination, and combined with tungsten carbon powder, which solved the problem of uneven dispersion of graphene in cemented carbide and significantly improved the strength and toughness of cemented carbide.
Patent Information
- Application Number
- CN202411926051.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
When graphene is mixed into cemented carbide, the graphene is unevenly dispersed, resulting in limited toughening and strengthening effect of cemented carbide. At the same time, the existing treatment methods have problems of environmental pollution and process complexity.
Through hydrothermal reaction and high-thermal reduction and calcination, GO/Co composite powder was prepared and combined with tungsten carbon powder to reduce density differences between components and improve the dispersion of graphene and the flake morphology.
The good dispersion of graphene in cemented carbide and the retention of sheet-layer morphology has been achieved, which significantly improves the strength and toughness of cemented carbide, and avoids settlement agglomeration and environmental pollution problems.
Smart Images

Figure CN119710344A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cemented carbide, and in particular to a cemented carbide material containing graphene oxide and a preparation method thereof. Background Art
[0002] Graphene is a sp 2 The two-dimensional carbon nanomaterial formed by the periodic arrangement of hybrid carbon atoms in a hexagonal shape has a single-layer thickness of only 0.335nm, which is the thinnest, strongest and hardest material found so far. Its elastic modulus can reach 1100GPa and its tensile strength is 125GPa. In the field of cemented carbide, graphene has become a very potential reinforcement phase due to its small size and excellent mechanical properties. It has been found that adding a small amount of graphene to cemented carbide can significantly improve its transverse fracture strength and fracture toughness while maintaining high hardness of cemented carbide.
[0003] However, due to the large specific surface area of graphene, in order to maintain a stable state with low energy, graphene powder is very easy to agglomerate under the action of van der Waals force, and the dispersion is poor, which is not conducive to the full play of the toughening and strengthening effect of graphene. In order to solve the above-mentioned problems of easy agglomeration and poor dispersion of graphene, the existing treatment methods are mainly divided into the following two types: one is to add graphene dispersants, such as hexadecyltrimethylammonium bromide, N-methylpyrrolidone and other organic solvents, to improve the dispersion effect of graphene; the other is to prepare modified graphene by chemical plating, so as to enhance the dispersion and bonding effect of graphene and cemented carbide powder.
[0004] The existing two methods mentioned above have the following problems: (1) When graphene is directly mixed with cemented carbide powder, sedimentation is very likely to occur, exacerbating the problem of graphene dispersion difficulties; (2) The treatment process involves the use of organic solvents, which poses a major environmental pollution problem, and the process is complex and costly. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of uneven dispersion of graphene that exists when graphene is mixed into cemented carbide.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a cemented carbide material containing graphene oxide, comprising the following steps:
[0008] S1 prepares a graphene suspension aqueous solution and a cobalt chloride aqueous solution respectively;
[0009] S2: mixing the graphene suspension aqueous solution with the cobalt chloride aqueous solution, heating, and performing a hydrothermal reaction to obtain a GO / CoC2O4 precursor;
[0010] S3: placing the GO / CoC2O4 precursor in a reducing atmosphere, heating and calcining to obtain a GO / Co composite powder;
[0011] S4: Mixing the GO / Co composite powder and the tungsten carbon powder and sintering them to obtain the cemented carbide material.
[0012] Preferably, in step S2, after the graphene suspension aqueous solution is mixed with the cobalt chloride aqueous solution, an ammonium oxalate aqueous solution is added, mixed evenly, and a hydrothermal reaction is carried out.
[0013] Preferably, in step S2, the hydrothermal reaction temperature is 70-90° C., and the hydrothermal reaction time is 10-15 h.
[0014] Preferably, in step S2, after the hydrothermal reaction is completed, it is first washed with deionized water and then dried at a constant temperature of 60-120°C to obtain the GO / CoC2O4 precursor.
[0015] Preferably, in step S3, the calcination temperature is 490-810° C., and the calcination time is 100-150 min.
[0016] Preferably, the specific treatment process of calcination is as follows:
[0017] First, heat to 500±10℃ at 10℃ / min, and keep at 500±10℃ for 30min;
[0018] Then heat to 650±10℃ at 5℃ / min and keep at 650±10℃ for 60min;
[0019] Finally, heat to 800±10℃ at 5℃ / min and keep at 800±10℃ for 30min.
[0020] Preferably, in step S3, reducing gas is continuously introduced during the calcination process, and the gas flow rate is 30-50 mL / min.
[0021] The hard alloy material containing graphene oxide prepared by the preparation method comprises, by mass, 65-93.5wt% of tungsten-carbon powder, 6-30wt% of cobalt powder and 0.5-5wt% of graphene oxide.
[0022] Preferably, the FASS particle size of the tungsten carbon powder is 0.2-1.0 μm.
[0023] The technical solution of the present invention has the following beneficial effects:
[0024] The present invention adopts cobalt chloride hexahydrate as a cobalt source, and through a hydrothermal reaction combined with a high-heat reduction calcination treatment method, graphene oxide is first uniformly dispersed in cobalt powder to prepare a GO / Co composite powder, and then the GO / Co composite powder is compounded and sintered with a cemented carbide powder. Since the density difference between graphene and cobalt material is smaller, the sedimentation problem caused by the density difference can be reduced. The GO / CoC2O4 precursor is first formed by hydrothermal reaction, and the CoC2O4 is reduced to elemental cobalt powder by calcination. This method can keep the graphene in a good lamellar morphology. The density difference between the GO / Co composite powder and the tungsten carbon powder is also small. Therefore, when the GO / Co composite powder is compounded with the tungsten carbon powder, the density difference between the components of the cemented carbide can be effectively reduced, and the sedimentation and agglomeration problem can be solved. Finally, the graphene can maintain a high dispersion in the cemented carbide powder and present an excellent lamellar morphology, which can effectively hinder the dissolution and precipitation between the tungsten carbon particles and prevent the growth of grains. The crack bridging of graphene can prevent the crack from expanding, and the strength and toughness of the cemented carbide are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a scanning electron microscope image of the GO / CoC2O4 precursor in Example 1;
[0026] Figure 2 is the XRD spectrum of the GO / Co composite powder in Example 1;
[0027] Figure 3 is a scanning electron microscope image of the GO / Co composite powder in Example 1;
[0028] Figure 4 is the metallographic diagram of the cemented carbide material in Example 1;
[0029] Figure 5 This is a flexural strength fracture morphology diagram of the sintered cemented carbide material in Example 1;
[0030] Figure 6 This is the Vickers hardness indentation diagram of the sintered cemented carbide material in Example 1;
[0031] Figure 7 This is the flexural strength fracture morphology of the sintered cemented carbide material in Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. Where specific conditions are not specified in the embodiments, they are carried out under conventional conditions or conditions recommended by the manufacturer; where the manufacturers of the instruments, equipment, reagents and raw materials used are not specified, they are all conventional products that can be purchased commercially.
[0033] The present invention provides a cemented carbide material containing graphene oxide, and a preparation method thereof comprises the following steps:
[0034] (1) Graphene oxide, cobalt chloride hexahydrate, ammonium oxalate and tungsten carbon powder are taken as raw materials. Graphene oxide and cobalt chloride hexahydrate are mixed respectively, placed in deionized water, and ultrasonically dispersed to obtain a uniformly dispersed graphene suspension aqueous solution and a cobalt chloride aqueous solution; the two solutions are then mixed at room temperature to obtain a GO / CoCl2·6H2O mixed aqueous solution.
[0035] The particle size of the tungsten carbon powder FASS is controlled at 0.2-1.0 μm; in the total raw materials, the content of tungsten carbon powder is 65-93.5wt%, the content of cobalt is 6-30wt%, and the content of graphene oxide is 0.5-5wt%. In the present invention, those skilled in the art can adjust the addition amount of the above raw material components according to the performance requirements of the product to obtain the corresponding required products.
[0036] (2) Add a certain amount of ammonium oxalate to the GO / CoCl2·6H2O mixed aqueous solution prepared above, use magnetic ultrasonic stirring for 30-60 minutes to make it evenly dispersed, and then add it to an autoclave containing tetrafluoroethylene, heat it to 70-90°C, and hydrothermally react for 10-15 hours; take the product after the hydrothermal reaction, wash it with deionized water for multiple times, and then place it in a constant temperature drying oven and dry it at 60-120°C to obtain a GO / CoC2O4 precursor.
[0037] (3) The GO / CoC2O4 precursor is placed in a N2 / H2 reducing atmosphere, heated to 490-810°C for high-temperature reduction calcination, the heating rate is 5-10°C / min, the calcination time is 100-150min, and the gas flow rate is controlled to be 30-50mL / min for continuous ventilation. After the calcination is completed, it is cooled to obtain a GO / Co composite powder.
[0038] Preferably, during the heating and calcining process, the specific treatment process of temperature and time is as follows:
[0039] First, heat to 500±10℃ at about 10℃ / min, and keep at 500±10℃ for 30min;
[0040] Then heat to 650±10℃ at about 5℃ / min, and keep at 650±10℃ for 60min;
[0041] Finally, the mixture was heated to 800±10℃ at a rate of about 5℃ / min and kept at 800±10℃ for 30min. Through strict temperature control, the reduction effect of CoC2O4 can be improved, and finally a GO / Co composite powder with good morphology and more uniform dispersion is presented.
[0042] (4) The GO / Co composite powder is mixed with tungsten carbon powder, and wet-milled, dry-granulated, pressed, and sintered in sequence to obtain a high-strength and high-toughness cemented carbide material containing graphene oxide.
[0043] In the present invention, a graphene and cobalt composite powder is first prepared by hydrothermal and high-temperature reduction calcination. Since the density difference between graphene and cobalt material is smaller, the sedimentation problem caused by the density difference can be reduced. A composite GO / CoC2O4 precursor is first formed by hydrothermal reaction, and the CoC2O4 therein is reduced to elemental cobalt powder by calcination. This method can keep the graphene in a good lamellar morphology. The density difference between the GO / Co composite powder and the tungsten carbon powder is also small. Therefore, when the GO / Co composite powder is compounded with the tungsten carbon powder, the density difference between the components of the cemented carbide can be effectively reduced, and the sedimentation problem can be solved. Finally, the graphene maintains a high dispersion in the cemented carbide powder and presents an excellent lamellar morphology, so that the strength and toughness of the cemented carbide are significantly improved.
[0044] Example 1
[0045] According to WC-6Co-0.5wt% GO, tungsten-carbon powder, cobalt chloride hexahydrate and graphene oxide are taken, and the particle size of tungsten-carbon powder FASS is about 0.8μm. First, cobalt chloride hexahydrate with a purity of ≥99.5% is placed in deionized water, ultrasonically dispersed to prepare a 1mol / L cobalt chloride hexahydrate aqueous solution; then, graphene oxide with a purity of ≥99.9% is placed in deionized water, ultrasonically dispersed to prepare a 10mg / mL graphene suspension aqueous solution.
[0046] The cobalt chloride hexahydrate aqueous solution and the graphene suspension aqueous solution prepared above were mixed at room temperature to obtain a GO / CoCl2·6H2O mixed aqueous solution; then, the ammonium oxalate aqueous solution was added to the GO / CoCl2·6H2O mixed aqueous solution at a molar ratio of ammonium oxalate to cobalt ions of 1:1, and magnetic ultrasonic stirring was performed for 50 minutes. Then, the mixture was transferred into a tetrafluoroethylene autoclave and heated to 80°C for hydrothermal reaction. After reacting for 12 hours, the reaction material was placed in a centrifuge and washed with deionized water for 3 times at a speed of 1000 rpm, each washing time being 5 minutes. The washed material was placed in a constant temperature drying oven at 60°C and fully dried to obtain a GO / CoC2O4 precursor.
[0047] The GO / CoC2O4 precursor was placed in a tubular furnace with an equal volume of N2 / H2 mixed atmosphere, and the temperature was first raised to 500°C at 10°C / min and kept at this temperature for 30 minutes; then raised to 650°C at 5°C / min and kept at this temperature for 60 minutes; finally raised to 800°C at 5°C / min and kept at this temperature for 30 minutes; during this period, the mixed gas was continuously introduced, and the gas flow rate was 30 mL / min. After the calcination, the GO / Co composite powder was obtained by cooling the furnace.
[0048] The GO / Co composite powder was mixed with tungsten carbon powder, and wet grinding was performed using ethane as the wet grinding medium and paraffin as the molding agent at a ball-to-material ratio of 4:1. After 24 hours of wet grinding, the material was unloaded, dried and granulated, and pressed into blocks. The blocks were placed in a low-pressure sintering furnace and heated to 1410±10°C at a heating rate of 2°C / min, and 5MPa argon was introduced for sintering. The insulation time was 60 minutes, and the mixture was then cooled to room temperature with the furnace, and the sintered product was taken out, which was the cemented carbide material.
[0049] Example 2
[0050] Take tungsten-carbon powder, cobalt chloride hexahydrate and graphene oxide according to WC-6Co-1.0wt% GO, and the particle size of tungsten-carbon powder FASS is about 1μm. First, take 66.1g of cobalt chloride hexahydrate with a purity of ≥99.5%, place it in deionized water, and ultrasonically disperse it to make a 1mol / L cobalt chloride hexahydrate aqueous solution; then take 5g of graphene oxide with a purity of ≥99.9%, place it in deionized water, and ultrasonically disperse it to make a 10mg / mL graphene suspension aqueous solution.
[0051] The cobalt chloride hexahydrate aqueous solution and the graphene suspension aqueous solution prepared above were mixed at room temperature to obtain a GO / CoCl2·6H2O mixed aqueous solution; 70 g of ammonium oxalate was fully dissolved in deionized water to obtain an ammonium oxalate aqueous solution, and added to the GO / CoCl2·6H2O mixed aqueous solution, magnetically ultrasonically stirred for 60 minutes, and then transferred to a tetrafluoroethylene autoclave, heated to 80°C for hydrothermal reaction, and after reacting for 12 hours, the reaction material was placed in a centrifuge, washed with deionized water for 3 times at a speed of 1000 rpm, each washing time being 5 minutes, and the washed material was placed in a constant temperature drying oven at 80°C to be fully dried to obtain a GO / CoC2O4 precursor.
[0052] The GO / CoC2O4 precursor was placed in a tubular furnace with an equal volume of N2 / H2 mixed atmosphere, and the temperature was first raised to 500°C at 10°C / min and kept at this temperature for 30 minutes; then raised to 650°C at 5°C / min and kept at this temperature for 60 minutes; finally raised to 800°C at 5°C / min and kept at this temperature for 30 minutes; during this period, the mixed gas was continuously introduced, and the gas flow rate was 30 mL / min. After the calcination, the GO / Co composite powder was obtained by cooling the furnace.
[0053] The GO / Co composite powder was mixed with 465g of tungsten carbon powder, and wet grinding was carried out using ethane as the wet grinding medium and paraffin as the molding agent at a ball-to-material ratio of 4:1. After 24 hours of wet grinding, the material was unloaded, dried and granulated, and pressed into blocks. The blocks were placed in a low-pressure sintering furnace and heated to 1410±10℃ at a heating rate of 2℃ / min, and 5MPa argon was introduced for sintering. The insulation time was 60min, and the mixture was then cooled to room temperature with the furnace, and the sintered product was taken out, which was the cemented carbide material.
[0054] Example 3
[0055] Take tungsten-carbon powder, cobalt chloride hexahydrate and graphene oxide according to WC-10Co-0.5wt% GO, and the particle size of tungsten-carbon powder FASS is about 1μm. First, take 110.2g of cobalt chloride hexahydrate with a purity of ≥99.5%, place it in deionized water, and ultrasonically disperse it to make a 1mol / L cobalt chloride hexahydrate aqueous solution; then take 2.5g of graphene oxide with a purity of ≥99.9%, place it in deionized water, and ultrasonically disperse it to make a 10mg / mL graphene suspension aqueous solution.
[0056] The cobalt chloride hexahydrate aqueous solution and the graphene suspension aqueous solution prepared above were mixed at room temperature to obtain a GO / CoCl2·6H2O mixed aqueous solution; 120 g of ammonium oxalate was taken and fully dissolved in deionized water to obtain an ammonium oxalate aqueous solution, and the ammonium oxalate aqueous solution was added to the GO / CoCl2·6H2O mixed aqueous solution, magnetically ultrasonically stirred for 60 minutes, and then transferred to a tetrafluoroethylene autoclave and heated to 90°C for hydrothermal reaction. After reacting for 10 hours, the reaction material was placed in a centrifuge and washed with deionized water for 3 times at a speed of 1000 rpm, each washing time being 5 minutes. The washed material was placed in a constant temperature drying oven at 80°C and fully dried to obtain a GO / CoC2O4 precursor.
[0057] The GO / CoC2O4 precursor was placed in a tubular furnace with an equal volume of N2 / H2 mixed atmosphere, and the temperature was first raised to 500°C at 10°C / min and kept at this temperature for 30 minutes; then raised to 650°C at 5°C / min and kept at this temperature for 60 minutes; finally raised to 800°C at 5°C / min and kept at this temperature for 30 minutes; during this period, the mixed gas was continuously introduced, and the gas flow rate was 30 mL / min. After the calcination, the GO / Co composite powder was obtained by cooling the furnace.
[0058] The GO / Co composite powder was mixed with 447.5g of tungsten carbon powder, and wet grinding was carried out using ethane as the wet grinding medium and paraffin as the molding agent at a ball-to-material ratio of 4:1. After 24 hours of wet grinding, the material was unloaded, dried and granulated, and pressed into blocks. The blocks were placed in a low-pressure sintering furnace and heated to 1410±10℃ at a heating rate of 2℃ / min, and 5MPa argon was introduced for sintering. The insulation time was 60min, and the mixture was then cooled to room temperature with the furnace, and the sintered product was taken out, which was the cemented carbide material.
[0059] Comparative Example 1
[0060] Take tungsten carbon powder, cobalt powder and graphene oxide according to WC-10Co-0.5wt%GO, and the FASS particle size of tungsten carbon powder and cobalt powder is about 1μm. Take 447.5g tungsten carbon powder, 50g cobalt powder and 2.5g graphene oxide, first mix the tungsten carbon powder with graphene oxide powder, use hexane as wet grinding medium, and wet grind at a ball-to-material ratio of 4:1. After wet grinding for 12 hours, add adhesive cobalt powder and molding agent paraffin. After continuing wet grinding for 12 hours, unload, dry and granulate, and press into blocks. In a low-pressure sintering furnace, heat up to 1410℃±10℃ at a heating rate of 2℃ / min, and pass 5MPa Ar gas for pressure sintering. The heat preservation time is 60min, and then cool to room temperature with the furnace, take out the sample, and obtain a cemented carbide material.
[0061] In this comparative example, graphene oxide is first mixed with tungsten carbon powder with a large density difference. The traditional wet grinding process cannot disperse the graphene evenly, and the large density difference exacerbates the agglomeration of graphene. Finally, in the sintered alloy, the original lamellar single-element graphene agglomerates to form a graphite phase, which deteriorates the mechanical properties of the alloy. The bending strength fracture morphology of the alloy in this comparative example is shown in FIG. Figure 7 As shown, it can be clearly seen that the graphene structure is not evenly dispersed and aggregated.
[0062] Comparative Example 2
[0063] Take tungsten carbon powder, cobalt powder and graphene oxide according to WC-10Co-0.5wt% GO, and the FASS particle size of tungsten carbon powder and cobalt powder is about 1μm. Take 447.5g tungsten carbon powder, 50g cobalt powder and 2.5g graphene oxide, mix the three at the same time, use ethane as wet grinding medium, paraffin as molding agent, wet grind at a ball-to-material ratio of 4:1, wet grind for 24h, unload, dry granulate, press into blocks, place in a low-pressure sintering furnace, heat up to 1410±10℃ at a heating rate of 2℃ / min, and pass 5MPa argon for sintering, keep warm for 60min, then cool to room temperature with the furnace, take out the sintered product, that is, the cemented carbide material.
[0064] Comparative Example 3
[0065] Take tungsten carbon powder and cobalt powder according to WC-10Co, and the FASS particle size of tungsten carbon powder and cobalt powder is about 1μm. Take 450g tungsten carbon powder and 50g cobalt powder, mix them, use ethane as wet grinding medium, paraffin as molding agent, and wet grind them at a ball-to-material ratio of 4:1. After wet grinding for 24 hours, unload the materials, dry and granulate them, and press them into blocks. Place them in a low-pressure sintering furnace, raise the temperature to 1410±10℃ at a heating rate of 2℃ / min, and pass 5MPa argon gas for sintering. The insulation time is 60min, and then cool to room temperature with the furnace, take out the sintered product, which is the cemented carbide material.
[0066] Test example
[0067] Samples: Examples 1-3, Comparative Examples 1-3
[0068] (1) Figures 1 to 3 As shown, they are respectively the scanning electron microscope image of the GO / CoC2O4 precursor in Example 1, the XRD spectrum of the GO / Co composite powder, and the scanning electron microscope image of the GO / Co composite powder; Figures 4 to 6 As shown, they are respectively the metallographic diagram of the cemented carbide material in Example 1, the bending strength fracture morphology diagram of the sintered cemented carbide material, and the Vickers hardness indentation diagram of the sintered cemented carbide material; Figure 7 Shown is the bending strength fracture morphology of the sintered cemented carbide material in Comparative Example 1.
[0069] Depend on Figures 1 to 7 By comparison, it can be seen that in Comparative Example 1, graphene oxide is first mixed with tungsten carbon powder with a large density difference, and the graphene oxide is mixed into the cemented carbide powder by traditional mechanical mixing. The graphene is unevenly dispersed, and the graphene originally in lamellae aggregates into agglomerates to form a graphite phase in the sintered alloy, which deteriorates the material properties of the cemented carbide. The cemented carbide material in Example 1 has uniformly dispersed graphene in a lamellae form, which can effectively and fully exert the strengthening and toughening effect of graphene.
[0070] (2) Random sampling of the cemented carbide materials prepared in Examples 1-3 and Comparative Examples 1-3 was performed as test samples, and material properties such as strength and toughness of the samples were measured. The results are summarized in Table 1 below:
[0071] Table 1 Material properties test results of different samples
[0072] Sample Hardness (HRA) TRS(MPa) <![CDATA[Fracture toughness K IC (MPa·m 1 / 2 )]]> Impact toughness(J) Example 1 93.2 3286 11.2 4.3 Example 2 93.6 3482 13.3 4.8 Example 3 92.5 3940 15.2 6.2 Comparative Example 1 89.1 1420 8.9 1.9 Comparative Example 2 89.3 1500 9.3 2.1 Comparative Example 3 91.2 2900 9.1 2.9
[0073] From the material property test results in Table 1 above, it can be seen that the hardness and toughness of the cemented carbide materials prepared by the methods of Examples 1 to 3 are significantly higher than the material properties of the cemented carbide materials prepared in Comparative Examples 1 to 3. It can be explained that the cemented carbide material and the preparation method thereof proposed in the present invention can effectively solve the problem of limited strengthening and toughening effect of cemented carbide due to uneven dispersion after the introduction of graphene oxide.
[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cemented carbide material containing graphene oxide, characterized in that: The following steps are involved: S1 prepares a graphene suspension aqueous solution and a cobalt chloride aqueous solution respectively; S2: mixing the graphene suspension aqueous solution with the cobalt chloride aqueous solution, heating, and performing a hydrothermal reaction to obtain a GO / CoC2O4 precursor; S3: placing the GO / CoC2O4 precursor in a reducing atmosphere, heating and calcining to obtain a GO / Co composite powder; S4: Mixing the GO / Co composite powder and the tungsten carbon powder and sintering them to obtain the cemented carbide material.
2. The method for preparing a cemented carbide material containing graphene oxide according to claim 1, characterized in that: In step S2, after the graphene suspension aqueous solution is mixed with the cobalt chloride aqueous solution, an ammonium oxalate aqueous solution is added, mixed evenly, and a hydrothermal reaction is carried out.
3. The method for preparing a cemented carbide material containing graphene oxide according to claim 1, characterized in that: In step S2, the hydrothermal reaction temperature is 70-90° C., and the hydrothermal reaction time is 10-15 h.
4. The method for preparing a cemented carbide material containing graphene oxide according to claim 2, characterized in that: In step S2, after the hydrothermal reaction is completed, it is first washed with deionized water and then dried at a constant temperature of 60-120°C to obtain the GO / CoC2O4 precursor.
5. The method for preparing a cemented carbide material containing graphene oxide according to claim 1, characterized in that: In step S3, the calcination temperature is 490-810° C., and the calcination time is 100-150 min.
6. The method for preparing a cemented carbide material containing graphene oxide according to claim 5, characterized in that: The specific process of calcination is as follows: First, heat to 500±10℃ at 10℃ / min, and keep at 500±10℃ for 30min; Then heat to 650±10℃ at 5℃ / min and keep at 650±10℃ for 60min; Finally, heat to 800±10℃ at 5℃ / min and keep at 800±10℃ for 30min.
7. The method for preparing a cemented carbide material containing graphene oxide according to claim 1, characterized in that: In step S3, reducing gas is continuously introduced during the calcination process, and the gas flow rate is 30-50 mL / min.
8. A cemented carbide material containing graphene oxide, characterized in that: The preparation method is described in any one of claims 1 to 7.
9. The cemented carbide material containing graphene oxide according to claim 8, characterized in that: By mass, it comprises 65-93.5wt% of tungsten carbon powder, 6-30wt% of cobalt powder and 0.5-5wt% of graphene oxide.
10. The cemented carbide material containing graphene oxide according to claim 9, characterized in that: The FASS particle size of tungsten carbon powder is 0.2-1.0 μm.
Citation Information
Patent Citations
Preparation method of graphene reinforced metal-matrix composite
CN102329976A
Preparation method based on solid-phase reaction for capacitor electrode material
CN103274481A
Graphene-based three-dimensional macro body as well as preparation method and application thereof
CN105271211A
Co-Fe alloy / graphene compound material, as well as preparation method and application thereof
CN106783237A
Graphen / Mg nanoparticle composite material and preparation method thereof
CN107297512A
Cited By
Superfine hard alloy cutter material for high-temperature material processing and preparation method of superfine hard alloy cutter material
CN119913409A